2017
DOI: 10.1016/j.seizure.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjunctive vagus nerve stimulation in patients with Dravet syndrome: A meta-analysis of 68 patients

Abstract: Vagus nerve stimulation appears to reduce seizure frequency in patients with DS. Based on this preliminary analysis, controlled trials of VNS in this rare condition using patient-centric outcome measures are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Response to these treatment modalities has been mixed, but a recent meta-analysis of 13 case studies published in the literature reported that 53% of 68 patients with Dravet syndrome experienced at least 50% seizure reduction. 25 The exact time frame as to when to introduce such invasive treatment options is unclear but probably before the onset of severe brain dysfunction, which FDG-PET could demonstrate. In future studies, it would be also interesting to demonstrate if palliative treatment to reduce seizures could halt the progression of glucose hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Response to these treatment modalities has been mixed, but a recent meta-analysis of 13 case studies published in the literature reported that 53% of 68 patients with Dravet syndrome experienced at least 50% seizure reduction. 25 The exact time frame as to when to introduce such invasive treatment options is unclear but probably before the onset of severe brain dysfunction, which FDG-PET could demonstrate. In future studies, it would be also interesting to demonstrate if palliative treatment to reduce seizures could halt the progression of glucose hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis including 68 patients with Dravet syndrome treated with adjunctive VNS, 53% of patients experienced ≥ 50% reduction in seizures. 22 VNS was associated with a mean seizure reduction rate of 31% at 12 months in 8 pediatric patients with Dravet syndrome. 67…”
Section: Dravet Syndromementioning
confidence: 94%
“…In DS children, there are many studies that display a efficacy of ≥ 50 % seizure reduction with a VNS implant [58][59][60]. A meta-analysis on the efficacy of VNS on 68 DS patients (13 studies) was reported by Dibue-Adjei et al [59] and showed an average of 55.2 % seizure reduction in these patients.…”
Section: Treatmentmentioning
confidence: 99%